A Comparison of the Concept of the Rule of Law in Indonesia and Islamic Law - Azhari, Doni; Asmuni (Journal of Transcendental Law, 2023)
This research examines the idea of the rule of law in the theory of absolute liability and the perspective of Islamic law in Indonesia through comparative and conceptual analysis techniques. To compare and contrast the two, this research integrates the idea of the rule of law from general theory with the understanding of Islamic law. This research emphasizes the state’s initiative to incorporate the ideas of Islamic law into its legal framework. While the idea of the rule of law and the principles of Islamic law are relevant, combining the two presents both opportunities and obstacles. This research is innovative in how it blends these ideas in Indonesia’s diverse environment. The findings from this research can help create an inclusive and just rule of law.